Histamine concentration is involved in canine valvular disease (Veterinary Science Development, 2014)
It has been known since many years that there are histamine receptors (H) in the heart. Histamines display chronotropic and inotropic activity, cardiovascular diseases, and are thought to be a systemic inflammatory disease. During heart failure, the histamine concentration is elevated. In addition, H2 blockers prolonged the survival period for human patients with heart failure. The aim of this study was to evaluate whether blood concentration of histamine is associated with canine valvular disease (CVD). The histamine concentrations of dogs with CVD are significantly higher than those of healthy dogs. The histamine concentration gradually increases during CVD and is highly correlated with the grade of heart murmur. In conclusion, the histamine concentration was higher in the population of dogs with CVD compared with the healthy controls. Although the etiopathogenesis of CVD is complex and incompletely understood, it likely involves histamine. Ultimately additional studies are required to determine whether histamine blockers might be useful for the management of dogs with cardiac valvular disease.